Privatization and regional agglomeration effect on technical efficiency of Bangladesh manufacturing industry - Baten, Md Azizul; Rana, Masud; Das, Sumonkanti; Nesa, Kamarun (2007)
This paper examines how far private investment in manufacturing industries of Bangladesh, together with the spatial agglomeration of those industries affect technical efficiency over the period 1981-82 through 1999-2000 using a panel data.Using the Translog stochastic frontier model outlined by (Huang and Liu, 1994:171) we found that private and foreign investment play an important role in explaining technical inefficiency, whereas impact of agglomeration is negligible.The paper also explored whether the degree of private investment has a greater impact on technical efficiency where the domestic industry is characterized by comparatively high productivity.The mean technical efficiency in the period analyzed was estimated to be 56.8%.